The mere presence of cuckoos in breeding area alters egg-ejection decisions in Daurian redstarts. (21st September 2022) - Zhang, Jinggang; Santema, Peter; Li, Jianqiang; Feeney, William E; Deng, Wenhong; Kempenaers, Bart
Abstract: Brood parasitic cuckoos and their hosts serve as model systems for studying host–parasite coevolution. Egg-rejection behavior constitutes an effective defense against brood parasitism, but some host species show phenotypic plasticity in egg-rejection behavior. Direct exposure to a cuckoo near the nest can increase egg-rejection likelihood, and long-term studies have shown that increased the egg-rejection rates generally correlate with higher parasite prevalence. However, it remains unclear whether such increases result from interactions between parasites and hosts, as these can be surprisingly common, or whether the mere presence of cuckoos in the breeding area is sufficient. Daurian redstarts Phoenicurus auroreus are a common host of the common cuckoo Cuculus canorus that defend against cuckoo parasitism mainly by ejecting the parasitic egg from the nest. This species is unique, as its first breeding attempt of the year takes place before the arrival of cuckoos, excluding the possibility for direct interactions. We simulated the ambient presence of cuckoos or hoopoes Upupa epops (control) in sub-populations of redstarts during their first egg-laying period by presenting taxidermic models and playing back vocalizations. Redstarts in cuckoo-treated plots showed significantly higher egg-ejection rates than individuals in control plots, even though females in both groups were equally likely to recognize the parasitic egg. Among females that did recognize the parasitic egg, those exposed to the cuckoo treatment were more likely to eject it than those exposed to the control treatment. Our results demonstrate unequivocally that the mere presence of cuckoos in the environment is sufficient to provoke egg-ejection behavior. Abstract : Perceived presence of cuckoos in the environment is sufficient to produce egg-ejection behavior by Daurian redstarts. We presented taxidermy models and play-backs of vocalizations of common cuckoos to Daurian redstarts (with exposure to hoopoes as a control), prior to the cuckoos' arrival at the breeding ground. Redstarts exposed to cuckoos were both more likely to eject a foreign egg and to eject it more quickly than redstarts exposed to hoopoes.